Supporting the search for the CEP location with nonlocal PNJL models constrained by lattice QCD - Contrera, Gustavo Aníbal Gabriel (2016)
We investigate the possible location of the critical endpoint in the QCD phase diagram based on nonlocal covariant PNJL models including a vector interaction channel. The form factors of the covariant interaction are constrained by lattice QCD data for the quark propagator. The comparison of our results for the pressure including the pion contribution and the scaled pressure shift ∆P/T4vs.T/Tc with lattice QCD results shows a better agreement when Lorentzian form factors for the nonlocal interactions and the wave function renormalization are considered. The strength of the vector coupling is used as a free parameter which influences results at finite baryochemical potential. It is used to adjust the slope of the pseudocritical temperature of the chiral phase transition at low baryochemical potential and the scaled pressure shift accessible in lattice QCD simulations. Our study, albeit presently performed at the mean-field level, supports the very existence of a critical point and favors its location within a region that is accessible in experiments at the NICA accelerator complex.